Genetic variability in ADAM17/TACE is associated with sporadic Alzheimer’s disease risk, neuropsychiatric symptoms and cognitive performance on the Rey Auditory Verbal Learning and Clock Drawing Tests - Francesco Bruno; Mirella A. Aceto; Ersilia Paparazzo; Domenico Arcuri; Francesca Vozzo; Serena Mirante; Beatrice M. Greco; Teresa Serra Cassano; Paolo Abondio; Sonia Canterini; Antonio Malvaso; Alessandro Grecucci; et al. (PLoS ONE, 2025)
Recent studies have highlighted the significant role of ADAM17/TACE (encoded by ADAM17/TACE) in the pathogenesis of Alzheimer’s disease (AD). Yet, the relationship between ADAM17/TACE gene polymorphisms and AD was less studied. This study aims to analyse the relationship of ADAM17/TACE gene polymorphism with the risk, age of onset, neuropsychiatric manifestations, cognitive impairment, and medial temporal lobe atrophy in sporadic AD (sAD). This case–control association study was conducted in an Italian cohort consisting of 297 sAD patients and 316 controls. Seven tag-SNPs were selected and genotyped. Linear and logistic regression analyses were used to assess the association between parameters of interest and the genetic variability of ADAM17/TACE. After Bonferroni correction, our findings underscore the complexity of genetic influences of ADAM17/TACE on sAD, particularly the roles of rs12692385 in modulating sAD risk and the performance on the Rey Auditory Verbal Learning Test – delayed recall. In addition, rs13008101 significantly affected the performance on the Clock Drawing Test. Moreover, rs10179642 and rs35280016 were associated with a higher frequency and severity of hallucinations and agitation/aggression, respectively. These results contribute to a deeper understanding of the genetic underpinnings of sAD and may be useful for examining the risk of developing sAD, assessing cognitive deficits, neuropsychiatric symptoms, and informing new therapeutic strategies and future research targeting ADAM17/TACE.